ST. YOSEF SEBAGAI TELADAN PELAYAN PASTORAL - Tomas Lastari Hatmoko (Jurnal Pelayanan Pastoral, 2021)
St. Joseph in the Catholic Church has a special place as a protector of the universal Church. Coinciding with the Covid-19 pandemic crisis and the celebration of St. Joseph, the Apostolic Letter "Patris Corde" provides an overview, as well as a reflection on the personality and life of Father Joseph. By exploring the letter and writing of St. Joseph through literature study, it becomes clearly that his personality should be a lifestyle of pastoral servants. The sincerity and patronage of St. Joseph is the basic personality of a pastoral minister needed even in a difficult pandemic situation like this. The way of St. Joseph in facing his situation, it became an inspiration and model in data-based pastoral work and management of pastoral in the Church.